1982
DOI: 10.1161/01.res.50.6.870
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic mechanism in the large cat cerebral artery.

Abstract: The isolated cat cerebral arteries (basilar, middle cerebral, anterior cerebral, and internal carotid) were studied in vitro. ACh at low concentration (3 x 10(-8) to 3 x 10(-6) M) induced relaxation, and at high concentration (10(-5) to 3 x 10(-3) M) induced constriction of the arteries with endothelial cells. In contrast, concentration of any magnitude (10(-6) to 3 x 10(-3) M) induced constriction exclusively in arteries without endothelium. Atropine (3 x 10(-6) to 3 x 10(-5) M) blocked and physostigmine (3 x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0
1

Year Published

1985
1985
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 24 publications
6
64
0
1
Order By: Relevance
“…The vasocon striction may result from activation of muscarinic receptors located directly on the smooth-muscle cells (Lee, 1982). These findings suggest a direct link between the hyperpolarization and the dilation in response to ACh and imply that the endothelial cell-mediated response to exogenous ACh normally dominates the overall effect of muscarinic activa tion, even at high concentrations of ACh.…”
Section: Discussionmentioning
confidence: 84%
“…The vasocon striction may result from activation of muscarinic receptors located directly on the smooth-muscle cells (Lee, 1982). These findings suggest a direct link between the hyperpolarization and the dilation in response to ACh and imply that the endothelial cell-mediated response to exogenous ACh normally dominates the overall effect of muscarinic activa tion, even at high concentrations of ACh.…”
Section: Discussionmentioning
confidence: 84%
“…The platinum wire was bent into a U shape and anchored to a gate. The stainless-steel rod was connected to a strain gauge (UC2; Gould) for isometric recording of changes in force, as described in our previous report (Lee, 1982). The temperature of the Krebs solution equilibrated with 95% 02/5% CO2 was maintained at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The endothelial cells of the arterial ring segments were mechanically removed by a standard brief gentle rubbing of the intimal surface with a stainless-steel rod having a diameter (25-30 gauge) equivalent to the lumen of the arteries (Lee, 1982). The successful removal of endothe lial cells was verified by lack of acetylcholine (3 ILM) induced relaxation (Furchgott and Zawadzki, 1980;Lee, 1980).…”
Section: Removal Of Endothelial Cellsmentioning
confidence: 99%
“…In our developed method, we believe that it is rather easy to make a preparation by means of a variety of diameter sizes of cannulae even in the relatively small vessels, and it is easy to insert a cannula from one side. Lee (1982) reported that ACh caused a vasodilatation in the isolated cerebral arteries with endothelium and a vasoconstriction without endothelium. Busse et al (1983) suggested that prostaglandin I2 might be involved in the hypoxic endothelium-induced dilatation.…”
Section: Monkey Basilar Arterymentioning
confidence: 99%